Epipelon dynamics in a shallow lake through a turbid-and a clear- water regime - Cano, María Gabriela (2016)
Fil: Cano, María Gabriela. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina